2008
DOI: 10.1007/s11695-008-9444-8
|View full text |Cite
|
Sign up to set email alerts
|

Support Group Meeting Attendance is Associated with Better Weight Loss

Abstract: Patients in the ASGM group lose more weight than patients in the NASGM group. The importance of attending SGM should be incorporated in preoperative patient counseling and encouraged during postoperative follow-up visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
2
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 9 publications
1
62
2
9
Order By: Relevance
“…Se ha descrito que los pacientes que participan en intervenciones grupales pierden mayor peso que quienes lo hacen de manera individual (Orth, Madan, Taddeucci, Coday y Tichansky, 2008). El presente estudio, por ser piloto, no cuenta con grupo de comparación, por lo que se sugiere incluirlo en otras investigaciones.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Se ha descrito que los pacientes que participan en intervenciones grupales pierden mayor peso que quienes lo hacen de manera individual (Orth, Madan, Taddeucci, Coday y Tichansky, 2008). El presente estudio, por ser piloto, no cuenta con grupo de comparación, por lo que se sugiere incluirlo en otras investigaciones.…”
Section: Discussionunclassified
“…Diversos estudios (Buddeberg-Fischer, Klaghofer, Sigrist et al, 2004;Nicolai, Ippoliti, Petrelli, 2002;Hildebrant, 1998;Orth, Madan, Taddeucci, et al, 2008) indican que intervenciones tales como grupos psicoeducativos o de apoyo pueden mejorar los resultados de la cirugía bariátrica mediante la modificación conductual y ayudar a identificar aquellos pacientes que se encuentran en riesgo de desarrollar comorbilidades psiquiátricas.…”
Section: Introductionunclassified
“…9 Although only a few studies have reported on WLS support groups, the findings suggest that individuals who attend regular monthly meetings gain emotional support to embrace new eating behaviors and dietary compliance. 9,46 In addition, Orth et al 46 observed that regular support group participation was associated with greater weight loss than those who did not attend a support group.…”
Section: Eating and Exercise Behaviors In Post Roux-en-y Gb Patientsmentioning
confidence: 99%
“…Both LAGB and RYGB patients have greater weight loss 6 months and 1 year postoperatively when attending a postoperative support group regularly, and the number of groups attended positively correlates with 1-year weight loss for LAGB patients. [45][46][47][48] Support groups assist with problem identification and solving, education, motivational enhancement, and provision of bariatric-specific support. Often, they can also include patients' support people.…”
Section: 34mentioning
confidence: 99%